Pendekatan Sadd Adz-Dzari’ah Dalam Studi Islam - intan arafah intan arafah (Al - Muamalat: Jurnal Hukum dan Ekonomi Syariah, 2020)
This article discusses sadd adz-dzariah in Islamic studies. Sadd adz-dzariah is a method produced by previous ushul fiqh scholars in an effort to keep humans as fallen mukallaf from falling into damage. This is done by closing and blocking all the means, tools and wasilah that will be used for an act. This article concludes that in determining a legal goal that forbids to a goal, sadd adz-Dzari'ah has three main elements that need to be considered, namely: First, the goal or purpose that you want to be desired. If the goal is evil, then the path is forbidden, and if the goal is good then the way is obligatory. Second, the intention or motive seen from the point of view of the target. If the intention is to achieve what is lawful, then the law of the ingredients is lawful, and if the intention to be achieved is haram, then the path to take that path is also haram. Third, namely the result of an action done.